Participants' Explanations for Nonadherence in the FEM-PrEP Clinical Trial. (1st April 2016) - Corneli, Amy; Perry, Brian; McKenna, Kevin; Agot, Kawango; Ahmed, Khatija; Taylor, Jamilah; Malamatsho, Fulufhelo; Odhiambo, Jacob; Skhosana, Joseph; Van Damme, Lut
Abstract : Background: FEM-PrEP—a clinical trial of daily, oral emtricitabine/tenofovir disoproxil fumarate for HIV prevention among women in sub-Saharan Africa—did not show a reduction in HIV acquisition because of low adherence to the study pill. We conducted a follow-up study to identify reasons for nonadherence. Methods: Qualitative, semistructured interviews (n = 88) and quantitative, audio computer-assisted self-interviews (n = 224) were conducted with former FEM-PrEP participants in Bondo, Kenya, and Pretoria, South Africa. Thematic analysis was used to analyze the qualitative data, and descriptive statistics were used to describe audio computer-assisted self-interviews responses. Data are presented within the 5 categories of Ickovics' and Meisler's conceptual framework on adherence: (1) the individual, (2) trial characteristics and study pill regimen, (3) patient-provider relationship, (4) clinical setting, and (5) the disease. Results: Participants' explanations for nonadherence were primarily situated within 3 of the framework's 5 categories: (1) the individual, (2) trial characteristics and study pill regimen, and (3) the disease. Concerns about the investigational nature of the drug being tested and side effects were the prominent reasons reported for nonadherence. Participants also described being discouraged from taking the study pill by members of the community, their sexual partners, and other participants, primarily because of these same concerns. Limited acceptability of the pill's attributes influenced nonadherence for some participants as did concerns about HIV-related stigma. In addition, many participants reported that others continued in FEM-PrEP while not taking the study pill because of the trial's ancillary benefits and visit reimbursement—factors related to the clinical setting. Negative patient-provider relationships were infrequently reported as a factor that influenced nonadherence. Conclusions: Despite substantial study staff engagement with participants and communities, concerns about the study pill and discouragement from others seemed to have influenced nonadherence considerably. Alternative study designs or procedures and enhanced community engagement paradigms may be needed in future studies. Abstract : Supplemental Digital Content is Available in the Text.